2013
DOI: 10.1002/ece3.555
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and environmental influences on egg size and juvenile life‐history traits in Pacific salmon

Abstract: Life-history traits such as fecundity and offspring size are shaped by investment trade-offs faced by mothers and mediated by environmental conditions. We use a 21-year time series for three populations of wild sockeye salmon (Oncorhynchus nerka) to test predictions for such trade-offs and responses to conditions faced by females during migration, and offspring during incubation. In years when their 1100 km upstream migration was challenged by high water discharges, females that reached spawning streams had in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 54 publications
5
61
0
Order By: Relevance
“…While the correspondence between thermal tolerance and environmental conditions suggests local adaptation brought about by selection on additive genetic effects, our study suggests that an indirect genetic effect-mediated by egg size-could instead underlie the variation. Indeed, across many sockeye salmon populations, egg size is populationspecific and positively correlated with natural incubation temperatures [37] and juvenile thermal tolerance [36]. Heart rate varies considerably both within and between fish species, with resting f H being primarily determined by metabolic rate and haemodynamic requirements, and f Hmax being limited by mechanistic constraints such as pacemaker potential, excitation-contraction properties and myocardium structure [38].…”
Section: Discussionmentioning
confidence: 99%
“…While the correspondence between thermal tolerance and environmental conditions suggests local adaptation brought about by selection on additive genetic effects, our study suggests that an indirect genetic effect-mediated by egg size-could instead underlie the variation. Indeed, across many sockeye salmon populations, egg size is populationspecific and positively correlated with natural incubation temperatures [37] and juvenile thermal tolerance [36]. Heart rate varies considerably both within and between fish species, with resting f H being primarily determined by metabolic rate and haemodynamic requirements, and f Hmax being limited by mechanistic constraints such as pacemaker potential, excitation-contraction properties and myocardium structure [38].…”
Section: Discussionmentioning
confidence: 99%
“…Fecundity of sockeye salmon (Oncorhynchus nerka) has also been found to increase with increased female size (Braun et al 2013), consistent with my findings as large females were found to spawn farther north and at longer migration distances.…”
Section: Fecunditysupporting
confidence: 86%
“…Colder incubation temperatures were also found for the northern interior systems where not only did the eggs incubate at colder temperature, but temperature was colder for spawning and most likely for migration. Braun et al (2013) found that gonadal mass decreased with increased migration difficulties for sockeye salmon -a finding consistent with my study as migration is more difficult for adult salmon at warmer temperatures (Farrell et al 2008). Additionally, less energy is required for metabolic processes at colder temperature, thus there may be limited benefit of producing large eggs, allowing females to allocate energy to other processes such as producing more eggs and somatic growth (Stickland et al 1988;.…”
Section: Gonadal Somatic Indexsupporting
confidence: 78%
See 2 more Smart Citations